2019
DOI: 10.1116/1.5112777
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Atomic layer deposition of doped ZnO films

Abstract: This article reviews the process-structure-property relationship in doped ZnO thin films via atomic layer deposition (ALD). ALD is an important manufacturing-scalable, layer-by-layer, thin film deposition process that precisely controls dopant type and concentration at the nanoscale. ZnO is an important technological material, which can be doped to modulate structure and composition to tailor a wide variety of optical and electronic properties. ALD doped ZnO is viewed as a transparent conducting oxide for appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 228 publications
1
44
0
Order By: Relevance
“…It was observed that the intensity of (0 0 2) of the sALD-ZnO film increases with substrate temperature due to the lowest surface energy of it. This result indicates the crystal grows along the c axis of wurtzite structure due to (0 0 2) being the closest packing and energetically favorable plane in a wurtzite structure [34]. Therefore, the adatoms gain more energy at a higher temperature to overcome the energy barrier to get to the energetically favorable sites.…”
Section: Structural and Morphological Study Of Zno Filmsmentioning
confidence: 90%
“…It was observed that the intensity of (0 0 2) of the sALD-ZnO film increases with substrate temperature due to the lowest surface energy of it. This result indicates the crystal grows along the c axis of wurtzite structure due to (0 0 2) being the closest packing and energetically favorable plane in a wurtzite structure [34]. Therefore, the adatoms gain more energy at a higher temperature to overcome the energy barrier to get to the energetically favorable sites.…”
Section: Structural and Morphological Study Of Zno Filmsmentioning
confidence: 90%
“…The review papers on ZnO grown by ALD published to date are mainly devoted to the chemistry of the growth process, crystallinity of the ZnO films, or external donor doping for transparent conductive oxide applications …”
Section: Introductionmentioning
confidence: 99%
“…The obtained films have density values in the range of 5.3 -5.8 g.cm -3 , which is similar to the ZnO density. 9,10 As shown in the Supporting Information (Figure S3), TZO films adopt either a polycrystalline ZnO wĂŒrtzite structure (n1 ≄ 2) or a ZnTiO3 nanocrystalline one (n1 = 1). 31 All TZO films are transparent in the visible range (transmittance values above 80% in the 300-1200 nm region) with optical gap values between 3.2 and 3.7 eV, which is in agreement to previously reported results.…”
Section: Influence Of the Cycle Ratio {Tio2}:{zno} And The Film Thickmentioning
confidence: 99%
“…5,6 Both undoped and doped zinc oxide have been extensively investigated by ALD. 9,10 Typically, diethylzinc (DEZ) and deionized water (H2O) are used as precursors for Zn and O atom sources. Doped materials are usually obtained by inserting a dopant growth cycle in between an integer number of ZnO cycles, leading to what is referred to as an ALD "supercycle".…”
Section: Introductionmentioning
confidence: 99%